2010
DOI: 10.1209/0295-5075/89/47004
|View full text |Cite
|
Sign up to set email alerts
|

An alternative interpretation of recent ARPES measurements on TiSe 2

Abstract: Recently there has been a renewed interest in the charge density wave transition of TiSe2, fuelled by the possibility that this transition may be driven by the formation of an excitonic insulator or even an excitonic condensate. We show here that the recent ARPES measurements on TiSe2 can also be interpreted in terms of an alternative scenario, in which the transition is due to a combination of Jahn-Teller effects and exciton formation. The hybrid exciton-phonons which cause the CDW formation interpolate betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 25 publications
7
55
0
Order By: Relevance
“…The presence and importance of excitons on the CDW order has been extensively discussed for the undoped compound 1T-TiSe 2 at ambient pressure [11,[14][15][16][43][44][45][46][47]. Below, we demonstrate theoretically that the pressure dependence of hybridazation between exciton and phonon modes can explain our experimental observations throughout the full , phase diagram.…”
Section: Tise 2 Under Pressuresupporting
confidence: 51%
“…The presence and importance of excitons on the CDW order has been extensively discussed for the undoped compound 1T-TiSe 2 at ambient pressure [11,[14][15][16][43][44][45][46][47]. Below, we demonstrate theoretically that the pressure dependence of hybridazation between exciton and phonon modes can explain our experimental observations throughout the full , phase diagram.…”
Section: Tise 2 Under Pressuresupporting
confidence: 51%
“…The second viewpoint treats the CDW state exclusively within the electron-phonon coupling framework of a band-type Jahn-Teller (JT) instability [29,30]. Both viewpoints received some experimental support recently through the analysis of the ARPES spectra [6,26,31], with some evidence that both mechanisms might be working simultaneously, and even cooperatively [31,32]. Irrespective of the true nature of the CDW state the pressure and doping will affect it differently.…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…The lattice plays an important role in the formation of the CDW in undoped TiSe 2 at ambient pressure [8][9][10][11][12][13][14][15][16][17] , as can be seen for example by the observation in quasi-elastic x-ray scattering experiments of a softening of the L − 1 phonon mode associated with the CDW distortion 18 . At the same time it is clear that excitons also are an indispensable ingredient in the description of this system 16,17,[19][20][21][22][23] , as witnessed for example by the large transfer of spectral weight to backfolded bands in ARPES measurements of the CDW phase 23 . In this context, the recent discoveries of superconductivity in the intercalated compound Cu x TiSe 2 by Morosan et al 24,25 , and in pure TiSe 2 under pressure by Kusmartseva et al 26 , are of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…We recently introduced a generic model system to study the effect of the interplay between exciton formation and electron-phonon coupling on the formation of CDW order 16,17,31 . Within this model it was shown that excitons can compete, coexist or even cooperate with phonons to drive the transition.…”
Section: Introductionmentioning
confidence: 99%